ChemInform Abstract: The Alternative Route to Enantiopure Multicomponent Reaction Products: Biocatalytic or Organocatalytic Enantioselective Production of Inputs for Multicomponent Reactions. Issue 45 (23rd October 2014) - Banfi, Luca; Basso, Andrea; Moni, Lisa; Riva, Renata
Abstract Review: [52 refs.